Understanding wine chemistry - Waterhouse, Andrew Leo; Jeffery, David W. 1972-; Sacks, Gavin L. 1978- (John Wiley & Sons Ltd., 2024)
Wine making is essentially a chemical process. It involves a chemical reaction in which sugars from grapes are turned to alcohol and carbon dioxide in the presence of yeast. There are many other chemical processes going on which affect the strength, appearance, colour and taste of the wine. Wine chemistry explains the flavor, balance, colour, stability that was once only possible through subjective description"--